Frontiers of propulsion science - Millis, Marc G.; Davis, Eric W. (Progress in astronautics and aeronautics ;, 2009)
This books is the first compilation of emerging science relevant to such notions as space drives, warp drives, gravity control, and faster-than-light travel - the kind of breakthroughs that would revolutionize spaceflight and enable human voyages to other star systems. Although these concepts might sound like science fiction, they are appearing in growing numbers in reputable scientific journals.